Increases in early discharge following acute coronary syndrome hospitalisations and associated clinical outcomes in New Zealand between 2006 and 2015: ANZACS‐QI‐43 study. Issue 8 (22nd August 2021) - Wang, Tom Kai Ming; Grey, Corina; Jiang, Yannan; Bullen, Christopher; Jackson, Rod; Kerr, Andrew
Abstract: Background: International guidelines recommend early discharge for uncomplicated acute coronary syndrome (ACS) patients within 3 days; however, there is a paucity of contemporary literature regarding the safety of this strategy. Aims: To report the trends in the proportion of ACS hospitalisations discharged within 3 days and their outcomes in New Zealand. Methods: ACS hospitalisations 2006–2015 using national routinely collected data were categorised by length of stay (LOS) into ≤3, 4–5 and >5 days, excluding deaths during the index admission. Trend analysis of death, cardiovascular and bleeding events and their composites (net adverse clinical events) at 30‐day and 1‐year post‐discharge were performed using generalised linear mixed regression models adjusting for covariates by LOS subgroups. Results: Among 130 037 ACS hospitalisations, LOS ≤ 3 days increased from 32% in 2006 to 44% in 2016. This trend was observed for all demographics, ACS subtypes and management strategies. Event rates at 30 days and 1 year were the lowest for the LOS ≤3 days subgroup (all‐cause mortality 1.6% and 9.1% respectively). Thirty‐day and 1‐year all‐cause mortality rates were unchanged over time for this subgroup (adjusted odds ratio (95% confidence interval) of 1.011 (0.985–1.038) and 0.991 (0.979–1.003)), while net adverse clinical event rates significantly decreased (0.962 (0.950–0.973) and 0.972 (0.964–0.980) respectively). Conclusion: There was a substantial increase in early discharge post‐ACS over 10 years. These patients were associated with reduction in adverse clinical events up to 1 year and no increase in all‐cause mortality. These findings from a comprehensive national register suggest that guideline recommendations on early discharge after uncomplicated ACS are safe and appropriate.